Comparing spiraling‐ and transport‐based approaches to estimate in‐stream nutrient uptake length from pulse additions. Issue 7 (29th July 2021) - Finkler, Nícolas Reinaldo; Gücker, Björn; Boëchat, Iola Gonçalves; Tromboni, Flavia; Thomas, Steven Arnold; Mendes, Ludmilson Abritta; Lima, Daniel Moura Fontes; Covino, Tim; Emanuelson, Karin; Ponce de León, Claudia; Fernandes Cunha, Davi Gasparini
Abstract: The distance that a nutrient travels as a solute before its removal from the stream water column is known as the uptake length ( S W ), which is a functional indicator of environmental quality and integrity. Among nutrient enrichment methods, instantaneous nutrient addition (e.g., slug or pulse) have been proposed as an alternative to plateau and labeled nutrient approaches. Two approaches have been commonly used to estimate S W and its associated metrics (i.e., areal uptake rate, U ; and uptake velocity, V f ) from pulse additions: the spiraling approach, based on the longitudinal variation in nutrient concentrations, and the transport modeling approach, based on the advective and dispersive transport of solutes. However, little is known in how the choice of such analytical methods impacts the estimation of stream uptake parameters and the conclusions we draw from them. Here, we estimated the S W and V f of ammonium‐nitrogen (NH4 ‐N) and soluble reactive phosphorus (SRP) from 16 pulsed additions conducted in four low‐order streams in southeastern Brazil. We compared metrics estimated by the Tracer Additions for Spiraling Curve Characterization (TASCC) and the One‐Dimensional Transport with Inflow and Storage (OTIS) methods, based on the spiraling‐ and transport‐based approaches, respectively. The TASCC:OTIS S W ratio averaged 0.71 for NH4 ‐N and 1.01 for SRP, whereas the mean of TASCC:OTIS V f ratio was 2.04 for NH4 ‐N and 1.03 for SRP. The results showed that both S W and V f estimates differed significantly between methods for NH4 ‐N, but no statistical differences were observed in SRP estimates. In our study, we highlighted the significant effects of transient storage and variable nutrient concentration on pulsed enrichments. Such information should be considered when choosing which method is appropriate to use for a particular site. Differences between modeling approaches must be addressed when comparing methods to expand our knowledge on broad temporal and spatial patterns of in‐stream nutrient uptake.